Broiler Chicken Performance Given Moringa (Moringa oliefera Lam) and Sambiloto (Andrographis paniculata) Leaf Extract in Drinking Water - Puji Astuti; Diwi Acita Irawati (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
This study aimed to determine the response of Moringa leaf extract (Moringa oleifera) and Sambiloto extract (Andrographis paniculata) in drinking water on the performance of broiler chickens. The research was carried out at the Animal Practice Uni) of the Karanganyar Animal Husbandry Academy. The research material was broiler chickens aged 4 days with an initial weight of 93.7 grams/head, as many as 60 chickens with 4 treatments and 3 replications for each replication of 5 chickens. The treatment applied was the administration of Moringa leaf extract and sambiloto as much as 5 ml/liter of drinking water, namely: T0: control treatment, T1: administration of bitter extract, T2: administration of Moringa and bitter extract (1: 1), and T3: administration of Moringa extract. The variables observed were broiler chicken performance including drinking water consumption, feed consumption, body weight gain, and feed conversion. The data obtained were statistically analyzed using a completely randomized design with a unidirectional pattern, the differences between treatments were calculated using the Duncan Multiple Region Test. The results showed that feed consumption was significantly different (P<0.05), drinking water consumption was not significantly different (P>0.05), body weight gain was significantly different (P<0.05), and feed conversion was significantly different (P<0.05). Feed consumption (grams/head/day) T0 = 95.23; T1= 91.4; T2 = 90.19 and T3 = 85.32, drinking water consumption (ml/head/day) T0 = 209.07; T1= 196.18; T2 = 196.49 and T3 = 197.04, body weight gain (grams/head/day) T0 = 62.16; T1= 61.18; T2 = 61.78 and T3 = 63.90, feed conversion T0 = 1.53; T1= 1.49; T2 = 1.46 and T3 = 1.34. The conclusion of this study was the administration of Moringa leaf extract and sambiloto affects the performance of broiler chickens.